Effects of Age-of-Acquisition on Proficiency in Polish Sign Language: Insights to the Critical Period Hypothesis - Tomaszewski, Piotr; Krzysztofiak, Piotr; Morford, Jill P.; Eźlakowski, Wiktor (Frontiers in Psychology, 2022)
This study focuses on the relationship between the age of acquisition of Polish Sign Language (PJM) by deaf individuals and their receptive language skills at the phonological, morphological and syntactic levels. Sixty Deaf signers of PJM were recruited into three equal groups (n=20): 1) a group exposed to PJM from birth from their deaf parents; 2) a group of childhood learners of PJM, who reported learning PJM between 4 and 8 years; 3) a group of adolescent learners of PJM, who reported learning PJM between 9 and 13 years. The PJM Perception and Comprehension Test was used to assess three aspects of language processing: phonological, morphological and syntactic. Participants were asked to decide whether a series of signs and sentences were acceptable in PJM. Results show that the age of PJM acquisition has a significant impact on performance on this task. The earlier deaf people acquire PJM, the more likely they were to distinguish signs and sentences considered permissible and impermissible in PJM by native signers. Native signers had significantly greater accuracy on the phonological, morphological and syntactic items than either the Childhood or the Adolescent signers. Further, the Childhood signers had significantly greater accuracy than the Adolescent signers on all three parts of the test. Comparing performance on specific structures targeted within each part of the test revealed that multi-channel signs and negative suffixes posed the greatest challenge for Adolescent signers relative to the Native signers. The above results provide evidence from a less-commonly studied signed language that the age of onset of first language acquisition affects ultimate outcomes in language acquisition across all levels of grammatical structure. In addition, this research corroborates prior studies demonstrating that the critical period is independent of language modality. Contrary to a common public health assumption that early exposure to language is less vital to signed than to spoken language development, the results of this study demonstrate that early exposure to a signed language promotes sensitivity to phonological, morphological and syntactic patterns in language.